2019
DOI: 10.1073/pnas.1904304116
|View full text |Cite
|
Sign up to set email alerts
|

Membrane perforation by the pore-forming toxin pneumolysin

Abstract: Pneumolysin (PLY), a major virulence factor of Streptococcus pneumoniae, perforates cholesterol-rich lipid membranes. PLY protomers oligomerize as rings on the membrane and then undergo a structural transition that triggers the formation of membrane pores. Structures of PLY rings in prepore and pore conformations define the beginning and end of this transition, but the detailed mechanism of pore formation remains unclear. With atomistic and coarse-grained molecular dynamics simulations, we resolve key steps du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 53 publications
(81 reference statements)
3
60
0
Order By: Relevance
“…As a member of the CDC family, PLO can bind and form pores on cholesterol-containing membranes. In pore formation, CDC monomers assemble into large oligomers and undergo an extensive structural change [18]. This oligomerization and structural change might have led to the loss of some conformational epitopes of the PLO monomer molecule and the decrease of accessibility of some linear epitopes in PLO monomers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a member of the CDC family, PLO can bind and form pores on cholesterol-containing membranes. In pore formation, CDC monomers assemble into large oligomers and undergo an extensive structural change [18]. This oligomerization and structural change might have led to the loss of some conformational epitopes of the PLO monomer molecule and the decrease of accessibility of some linear epitopes in PLO monomers.…”
Section: Discussionmentioning
confidence: 99%
“…CDCs are expressed as soluble monomers, which adhere to cholesterol-rich membranes by their D4, organize into closed rings as mediated by their D2 and D3, and form a prepore membrane protein complex. This event results in an extensive structural remodeling in which the D3 converses to transmembrane hairpins, the D2 structurally collapses, and the CDC's prepore complex forms a large oligomeric β-barrel and perforates the plasma membrane [18]. The role of D1 in pore forming remains unclear; however, the replacement of some amino acids impairs the hemolytic activity of PLO molecules [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, pneumolysin, a pore-forming toxin is the key virulence factor of Gram-positive bacteria (Streptococcus pneumoniae) and is considered to influence alveolar epithelial cells to stimulate the immune system by the release of danger-associated molecular patterns [136,137]. Nerlich et al [138] demonstrated that bacterially released pore-forming toxin pneumolysin could remarkably alter the ATP homeostasis of cells and lead to morphologic changes of mitochondria in alveolar epithelial cells of human in vitro.…”
Section: Mitochondrial Dna and Anti-bacterial Immunitymentioning
confidence: 99%
“…Pneumolysin is a pore-forming toxin produced by all clinical strains of S. pneumoniae [44]. It is thought to be responsible for much of the inflammation observed during pneumonia and the organ damage observed during disseminated infections.…”
Section: Multi-modal Protection: Prevention Of Disseminated Disease Amentioning
confidence: 99%